Framing systemic traffic violence: Media coverage of Dutch traffic crashes. (May 2020) - te Brömmelstroet, Marco
Abstract: Traffic crashes undeniably levy a significant and detrimental toll on contemporary societies. They are a disruption of every-day traffic order, and the specifics of their coverage in the media offer insights into how a society frames and perceives this underlying order. This study analysed the terms and frames that are used in 368 reports on traffic crashes in local Dutch newspapers. The coding is embedded in the larger debates about competing frames of mobility (efficiency versus justice), and informed by recent studies on traffic crash reporting. The study adds a novel geographical context to the Northern American focus of earlier work, and a broader scope of traffic crash types (including non-fatal crashes and all vehicle types). The reviewed articles support the previous findings that media coverage largely dehumanizes traffic crashes, presenting them more as glitches in the machine (efficiency) than human tragedies (justice). Crashes are presented as episodes instead of as part of a larger pattern, in a factual tone. Parties involved in a crash, and especially secondary parties are most often referred to as vehicles instead of persons and most often the headlines use a non-agentive grammar. However, the study also demonstrates that the way we currently study this coverage is limiting us in develop a full understanding of the complex nature of traffic crashes. To overcome this, we need to deploy mixed methods and a richer coding scheme that help us to get a better grip of the systemic violence of our contemporary traffic. Highlights: Media reporting on traffic crashes offers a potent lens to understand how we frame mobility I studied 368 news reports on all types of traffic crashes in Dutch local news media The study confirms the dehumanizing nature of reporting and a focus on an efficiency frame It also finds that current frameworks to study it might be too limited to cover the full complexity of traffic crashes We need more sensitivity in describing human agency vs. =systemic traffic violence inherent in a car based mobility system